2015
DOI: 10.5958/0973-970x.2015.00049.8
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of pathological conditions in the female genitalia of goats

Abstract: The present study was conducted with the aim to record the pathological conditions in the female genital tract of goats. A total of 660 female genital tracts of goats were collected randomly from various slaughter houses as well as from CIRG post-mortem house regardless of breed and age (3 months to 8 years old) of the animals. Out of total 660 samples collected and examined, 154 (23.32%) revealed different types of pathological conditions. Highest occurrence of pathological conditions was observed in the uter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 3 publications
0
13
3
Order By: Relevance
“…However, there was no statistical correlation in age and lesions between RS and WAD in this study. Pathological conditions of the uterus of RS (38.4%) and WAD (25.6%) were lower than earlier reports of 53.24%, 41.34% and 70% by [11] [14] and [29] in Iranian and India does, respectively, but higher than that reported [15] of 14.6% goats.…”
Section: Discussioncontrasting
confidence: 69%
See 4 more Smart Citations
“…However, there was no statistical correlation in age and lesions between RS and WAD in this study. Pathological conditions of the uterus of RS (38.4%) and WAD (25.6%) were lower than earlier reports of 53.24%, 41.34% and 70% by [11] [14] and [29] in Iranian and India does, respectively, but higher than that reported [15] of 14.6% goats.…”
Section: Discussioncontrasting
confidence: 69%
“…Results of the present study show that the occurrence of female genital lesions in the two breeds of 49.3% and 43.3%, respectively, were high compared to the findings of [11] [13] [22], in Indian goats [15], in Nigeria and [19] in Uganda, age is an important intrinsic factor that contributes to the distribution of reproductive abnormalities. This agrees with findings of [15] and [16] who reported that susceptibility to reproductive disease increases with age.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations